Part II. Drama / Choreography5. Theater Dance Atelier - Enache Lorette (Sciendo, 2017)
The substance of the spiritual and cultural life is the syncretism of the arts from the performer-spectator division, that was made concurrently with the "dance" segmentation into work and pleasure. Words were held in formulas, gestures and dance in rhythm. Today, dance is mostly seen as the art of gesture. However, it is remarkable to reflect at to what extent the dance, as an organic necessity, it could further develop into hermetic structures that would still require analyses and studies from researchers in the field. In today‟s theatrical landscape, this formula of artistic expression which was called theatre dance evolved so much so that gesticulations and body exploration became its core components.